Underlying structure of e-learning readiness among Palestinian secondary school teachers - Trayek, Fuad; Nordin, Mohamad Sahari; Tunku Ahmad, Tunku Badariah; Dwikat, Mohamad Am; Abulibdeh, Enas Said; Ghaus, Azmah; Muath, Asmar; Siti Salwa, Md. Sawari (2015)
This paper reports on the results of an exploratory factor analysis procedure applied on the elearning readiness data obtained from a survey of four hundred and seventy-nine (N = 479) teachers from secondary schools in Nablus, Palestine. The data were drawn from a 23-item Likert questionnaire measuring e-learning readiness based on Chapnick's conception of the construct. Principal axis factoring (PAF) with Promax rotation applied on the data extracted four distinct factors supporting four of Chapnick's e-learning readiness dimensions, namely technological readiness, psychological readiness, infrastructure readiness and equipment readiness. Together these four dimensions explained 56% of the variance. These findings provide further support for the construct validity of the items and for the existence of these four factors that measure e-learning readiness